2012
DOI: 10.1002/rcm.6465
|View full text |Cite
|
Sign up to set email alerts
|

Analytical challenges in the quantitative determination of 2H/1H ratios of methyl iodide

Abstract: We have refined an earlier method to measure the δ(2)H values of CH(3)I by GC/P/IRMS by adding a cold trap to remove HI. This approach should facilitate future experimentation with the measurement of CH(3)I liberated from natural samples for potentially diverse applications including forensic sourcing of wood and tree-wood-based reconstructions of source water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
(51 reference statements)
1
12
0
Order By: Relevance
“…The molecular background scan after HTC revealed considerable formation of H‐bearing byproducts from all halogen‐bearing compounds, confirming earlier observations . In general, hydrogen halides were the most abundant byproducts, followed by various hydrocarbons (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular background scan after HTC revealed considerable formation of H‐bearing byproducts from all halogen‐bearing compounds, confirming earlier observations . In general, hydrogen halides were the most abundant byproducts, followed by various hydrocarbons (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…F, Cl, Br, I) organics using conventional high‐temperature conversion (HTC) has been long fraught with difficulties, due to the formation of H‐containing byproducts as HF, HCl, HBr and HI (Fig. ) . Moreover, H 2 recovery from bi‐ and tri‐chlorinated ethylenes by traditional off‐line combustion to water and subsequent reduction to H 2 was recently reported to be non‐quantitative and affected by isotope fractionation .…”
Section: δ2h Values For N‐alkane and Diverse Halogen‐bearing Referencmentioning
confidence: 99%
“…The dD methoxyl signatures of lignin and pectin of the same plant sample are known to be similar (Greule and Keppler, 2011). dD methoxyl values can be measured by cleavage of the ether or ester moieties with hydroiodic acid (HI) to form the gaseous compound methyl iodide (CH 3 I) whose dD value is measurable by gas chromatography pyrolysis isotope ratio mass spectrometry (GC-P-IRMS) (Greule et al, 2008;Feakins et al, 2013b). For the purposes of brevity this procedure is hereafter referred to as the 'HImethod'.…”
Section: Introductionmentioning
confidence: 99%
“…Later this method was applied by Galimov et al and Krüger et al for measurements of the δ 13 C values of biogenic methoxy groups . In the last two decades the method has been employed for the precise and rapid δ 2 H and δ 13 C analysis of methoxy groups by gas chromatography/isotope ratio mass spectrometry (GC/IRMS) …”
Section: Introductionmentioning
confidence: 99%
“…24,32,33 In the last two decades the method has been employed for the precise and rapid δ 2 H and δ 13 C analysis of methoxy groups by gas chromatography/ isotope ratio mass spectrometry (GC/IRMS). 8,[34][35][36] The reported δ 2 H and δ 13 C values of plant-related methoxy groups range from −149 mUr 25 to −405 mUr 22 and from −7.1 mUr 25 to −77.2 mUr, 8 respectively. In addition, the δ 2 H and δ 13 C values of C 1 -groups from extraterrestrial matter such as meteorites (carbonaceous chondrites) have been shown to be in the range of +1054 ± 626 mUr and +43.2 ± 38.8 mUr, respectively.…”
mentioning
confidence: 99%